ReVwalk gamification for cerebral palsy kids - Mohamad Zikri Amin, Awang; Mohd Azrul Hisham, Mohd Adib (2021)
There are 3 level of disablility of CF kids, mild,moderate,severe.Duration of standing and walking. Walking distance by cp kids